Marcel Proust and in search of lost time: ethics of human existence and the world of medicine recovered - Figueroa, Gustavo (Acta Bioethica, 2022)
1. Marcel Proust´s In Search of Lost Time recounts the fiction of the “author’s” project-of-existence to become an artist. 2. The world of medicine is the area in which the fragility of man is expressed as being-referred-to-death. 3. The deceptive feeling of the power of good health intoxicates medicine, physicians, patients, relatives, treatments — irreverent depreciation toward the perishable. 4. The medical treatment of the agony of the “author’s” grandmother shows the central elements of the doctor-patient relationship in medicine at the beginning of the 20th century: cognitive, affective, operational, ethical, and social. 5. The “author” of the novel is not Marcel Proust and, although it is a fiction, it encourages today´s medical world to reflect on its fundamental bioethical foundations.